The Leadership of School Principals in Improving the Quality of Vocational High Schools in Tanjung Selor District, Bulungan Regency - Puji Surya Putra; Nurtanio Agus Purwanto (Green Publisher Indonesia, 2025)
This study analyzes the principal's leadership programs and strategies, the impact of implementation, as well as the supporting and inhibiting factors in improving school quality at SMK Negeri in Tanjung Selor District, Bulungan Regency. Using descriptive qualitative method, data were collected through in-depth interviews and observations, and analyzed using the interactive model of Miles, Huberman and Saldaña.The results showed that the principal implemented: (1) curriculum development based on industry needs, provision of educational facilities and infrastructure, and the creation of a safe and comfortable learning environment; (2) collaboration strategies with stakeholders, training, and awarding to improve school quality; (3) positive impacts in the form of increased teacher competence, cooperation with education policy makers, and educational innovation through partnerships; and (4) challenges such as limited resources, motivation, and conventional learning methods.In conclusion, industry-based curriculum development, adequate facilities, collaboration and training are key to improving quality, although there are still obstacles that need to be overcome.